THE EFFECTIVENESS OF USING FIELD TRIP TECHNIQUE TO THE WRITING SKILL FOR THE SENIOR HIGH STUDENTS - Saifudin S. Adam (Universitas Khairun, 2016)
The objective of this research is to find out whether there is significant difference in teaching writing skill between the second grade students of senior high school who are taught by using field trip technique and those who are not taught by using field trip technique.The effect field trip technique in teaching writing descriptive text is hoped to build students background knowledge through the real situation such bringing students outside the classroom so that the students can explore their mind through what they see and face directly. Field trip technique in teaching writing skill is an activity which involves students to share ideas through the school environment in order the students can achieve learning goal.This research is an experimental research which was held at SMA N 3 Kota Ternate. The experimental research involved two groups of students, they are experimental group and control group. The research subjects are the second year students of science class at SMA N 3 Kota Ternate. The sample of this research was taken randomly. The the experimental group belong to experimental group included of 30 students while the students of control group belong to control groupwas 30 students. Both classes were given pre-test at the beginning. Then, the students of experimental group were taught by using field trip activity while the control group is taught without field trip activity.The research findings indicated the results of the research, as follows: The analysis result of experimental class shows that the mean score of pre-test in experimental classis 45.47 and the means score of post-test is 71.82. It shows that the experimental class experiences improvement in their writing test, and the hypothesis testing indicates that the score of the experimental class students are higher than the control class. It can be seen that the value of p is 0.000 lower than the value at the significant level 0.5. or 0.000<0.05.Andvalue of p is 0.183. It is higher than 0.05 (0.1830>0.05). So the hypothesis testing indicates that the score of the experimental class students are significantly higher than that of the control class. It can be said that using field trip teaching writing descriptive is effective. Keywords: Outdoor Classroom Activity, Writing Skill and Descriptive Text.